2013
DOI: 10.1007/s11207-013-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Coronal Magnetic Field Using a Type II Solar Radio Burst

Abstract: The Type-II solar radio burst recorded on 13 June 2010 by the radio spectrograph of the Hiraiso Solar Observatory was employed to estimate the magnetic-field strength in the solar corona. The burst was characterized by a well pronounced band-splitting, which we used to estimate the density jump at the shock and Alfvén Mach number using the Rankine-Hugoniot relations. The plasma frequency of the Type-II bursts is converted into height [R] in solar radii using the appropriate density model, then we estimated the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
3
13
1
6
Order By: Relevance
“…The adoption of the central frequencies of the lower-frequency branch to estimate the heights of the radio source has accounted for our higher values. However, our results are different from those obtained by Vasanth et al (2014), who found a sharp decrease in the shock speed, from 820 km s −1 to 580 km s −1 , for 05:39 -05:41 UT (three and five minutes after the onset of the type II emission). Our estimates of the frequency drift rate using exponential fits on the intensity maxima of the radio emission may be responsible for these differences.…”
Section: Resultscontrasting
confidence: 99%
“…The adoption of the central frequencies of the lower-frequency branch to estimate the heights of the radio source has accounted for our higher values. However, our results are different from those obtained by Vasanth et al (2014), who found a sharp decrease in the shock speed, from 820 km s −1 to 580 km s −1 , for 05:39 -05:41 UT (three and five minutes after the onset of the type II emission). Our estimates of the frequency drift rate using exponential fits on the intensity maxima of the radio emission may be responsible for these differences.…”
Section: Resultscontrasting
confidence: 99%
“…The value is consistent with previous work (Vršnak et al 2002;Mancuso & Garzelli 2013;Kouloumvakos et al 2014;Vasanth et al 2014;Zucca et al 2014b), but it is more closely constrained in the present event by the combination of the type II spectrum and the stereoscopic CME modeling. Similar Mach numbers were derived from white-light observations (Bemporad & Mancuso 2010, 2011.…”
Section: Cme Shocksupporting
confidence: 92%
“…В настоящее время не вызывает сомнений, что солнечные радиовсплески II типа генерируются в области фронта ударных волн [1][2][3][4]. Часто на динамических спектрах можно наблюдать две близко расположенные полосы, ведущие себя схожим образом как по интенсивности, так и скорости дрейфа на протяжении десятков минут [2][3][4][5][6][7].…”
Section: Doi: 1031725/0552-5829-2019-427-430unclassified